PERAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PEMADAM KEBAKARAN KAB KARAWANG - Jaenudin Jaenudin; Dedi Mulyadi; Sungkono Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research examines the influence of work motivation on employee performance at the Karawang Regency Fire Department. Work motivation, as an internal drive that encourages employees to achieve organizational goals, is the main focus of this research. This research is based on the inconsistency of previous research findings regarding the influence of work motivation on employee performance in the firefighting sector. A quantitative method with a survey approach was used, involving 35 employees as a sample. Data was collected through questionnaires, observation and documentation. The research results show that work motivation has a significant influence on employee performance, proven through the t test and F test. This research concludes that work motivation is an important factor in improving employee performance at the Karawang Regency Fire Department.